Zn‐Incorporated Titanium Substrates with High Antibacterial Activity and Consecutive Release of Zinc. Issue 1 (2nd January 2023) - Lin, Xing; Jin, Kaihao; He, Liyin; Zhi, Hongfeng; Ying, Yunhui; Wang, Xiao; Wu, Yinqiu; Zhang, Jianfeng
Abstract: In this work, Zn‐incorporated titanium substrate with nano network structures was built, and its antibacterial activity against the gram positive and negative bacteria was tested. Ti plate was successively treated by hot alkaline, Zn 2+ ion‐exchange, and ZnO nanoparticles deposit, where alkaline treated Ti plate (NTi), Zn 2+ exchanged Ti plate (NZTi), Zn 2+ /ZnO incorporated Ti plate (NZZTi) were correspondingly generated. For Escherichia coli, the antibacterial percentage of NZTi and NZZTi after 24 h was 99.86 % and 99.98 %, while it was 99.95 % and 100 % for Staphylococcus aureus, respectively. The result disclosed that NZZTi have a bit better antibacterial activity than NZTi, which indicates that Zn 2+ shows fabulous antibacteria activity and the presence of ZnOnps can contribute the antibacterial ability of Ti plates, which agrees with result of NZZTi‐Cup antibacterial effect. The release tests of Zn 2+ after 8 days from NZZTi‐Cup disclosed that Zn‐incorporated Ti plate could consecutively release trace Zn ions. Abstract : The composite titanium matrix of zinc ion and nano zinc oxide with nano network structure was constructed, and its antibacterial rates against Escherichia coli and Staphylococcus aureus were 99.98 % and 100 %, respectively. In addition, the cup made of this material has excellent antibacterial activity and can continuously release trace Zn ions.